Paroxysmal sympathetic hyperactivity syndrome caused by Streptococcus intermedius meningoencephalitis in children: a case report and literature review - Huang, Qiuling; Zhou, Ruoyi; Zhang, Yean; Li, Jie; Yu, Feng (Frontiers in Pediatrics, 2024)
Introduction and importance: Paroxysmal sympathetic hyperactivity (PSH) syndrome often occurs with severe traumatic brain injury. However, it can also occur during infections, such as severe bacterial meningoencephalitis in children.Streptococcus intermedius is an aggressive, virulent, opportunistic pathogen. This species can cause meningoencephalitis in children, as reported in a few cases.Case information: A five-year-old boy with no relevant past medical history was admitted to a hospital because of a fever and progressive disturbance of consciousness.His head computed tomography scan and magnetic resonance imaging revealed extensive brain damage and an intraventricular abscess. A next-generation sequencing technology test performed on his cerebrospinal fluid revealed that the child's meningoencephalitis was caused by S. intermedius. During treatment, the child had clinical manifestations such as fever, tachycardia, tachypnea, diaphoresis, and hypertension. Changes in muscle tone and abnormal posture, which were misdiagnosed as epilepsy at the early treatment stage, were also observed; however, anti-epileptic treatment was ineffective. The child was diagnosed with PSH and received the appropriate treatment, and his symptoms eventually improved.Conclusions: To our knowledge, this is the first case report on PSH induced by S. intermedius meningoencephalitis. Early identification, diagnosis, and treatment of PSH are crucial.